Social Media Software as a Web-Based Department of Communication Means Mobile (Case Study Department of Information Engineering) - Rahayu, Muji (Jurnal Manajemen Informatika Medicom (JMI), 2024)
Information can be spread out to people directly or thought a media. Social media is often used to spread the information. Most of people need not special skills to use social media. A lack of direct communication among students causes the information ineffectively and ineffectively delivered. Therefore, the social media that is expected to help spread information and maintain communication among students is needed to design. The web mobile based social media for the departments was designed to help spread information in order to communicate information among students in an effective and efficient manner. The information was spread out through updating the user`s status on the social media. Morcover, the users also provided comments and suggestions on the comment line this software was developed further by adding a group feature live streaming in order to facilitate the users in sharing suggestions and information.